Modified calcium copper titanate nanofiber and epoxy composite dielectric material, preparation method and application thereof

CN122980207APending Publication Date: 2026-10-27ELECTRIC POWER RES INST OF GUANGDONG POWER GRID CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611412934.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是由于高介电常数的CCTO与低介电常数的环氧树脂基体之间存在极其巨大的介电常数突变,传统的单层有机界面无法建立介电常数逐级过渡的缓冲结构

Benefits of technology

本发明通过静电纺丝结合两阶段煅烧得到直径均匀、结晶度高的钛酸铜钙CCTO纳米纤维;随后在该钛酸铜钙纳米纤维表面依次原位包覆无机介电过渡层和有机相容层,构建得到满足介电常数自内向外逐级递减、具有电场缓冲结构的梯度介电界面层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122980207A_ABST
    Figure CN122980207A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of insulating materials, and discloses a modified calcium copper titanate nanofiber and an epoxy composite dielectric material, a preparation method and application, and comprises the following steps: step 1: coating an inorganic dielectric transition layer on the surface of the calcium copper titanate nanofiber, wherein the inorganic dielectric transition layer is one or two or more of a silicon dioxide layer, an aluminum oxide layer and a titanium oxide layer; step 2: coating an organic compatible layer on the surface of the calcium copper titanate nanofiber coated with the inorganic dielectric transition layer obtained in step 1 to obtain the required modified calcium copper titanate nanofiber, wherein the organic compatible layer is one or two or more of a polydopamine layer, an amino resin layer and an epoxy reactive polymer layer; the calcium copper titanate fiber network coated with a gradient dielectric interface in the obtained epoxy composite dielectric material effectively dissipates interface space charges through a carrier migration mechanism, in combination with nonlinear conductive characteristics, so that the charge dissipation time is shortened, the dielectric aging is inhibited, and the service life of equipment is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of insulating materials technology, specifically to a modified copper titanate calcium nanofiber and epoxy composite dielectric material, its preparation method, and its application. Background Technology

[0002] In high-voltage electrical equipment, advanced electronic devices, and new energy systems, dielectric materials are core components that determine the insulation and reliability of the equipment. Epoxy resin is widely used as a dielectric matrix material due to its excellent insulation, mechanical strength, and chemical stability. However, with the development of power systems towards higher voltage and larger capacity, and the miniaturization trend of electronic devices, traditional epoxy resin dielectrics face several key challenges.

[0003] Under high voltage or non-uniform electric fields, epoxy resins are prone to local electric field distortion due to material defects, interface polarization, or space charge accumulation, leading to partial discharge or even insulation breakdown. Traditional epoxy resins exhibit linear conductivity and dielectric constant, making it impossible to dynamically adjust charge transport paths based on electric field strength and actively suppress electric field concentration. However, in recent years, calcium copper titanate (CaCu3Ti4O) has been used in research... 12 CCTO (concentrated crystalline carbonyl ether) has become a research hotspot in the field of functional dielectrics due to its unique nonlinear conductivity. The conductivity of CCTO increases exponentially with the electric field strength, allowing it to automatically form conductive channels in high-field regions, diverting excess charge and achieving dynamic electric field equilibrium. Furthermore, one-dimensional nanofibers have a higher aspect ratio than particulate fillers, enabling the construction of three-dimensional percolation networks with low filler content while maintaining the mechanical properties of the matrix. However, CCTO nanoparticles are prone to aggregation and have weak interfacial bonding with the polymer matrix, leading to decreased electric field modulation efficiency. CCTO fibers synthesized using the traditional sol-gel method have low crystallinity and are difficult to control in terms of orientation distribution.

[0004] Existing technologies include methods for surface monolayer organic grafting modification of inorganic fillers using silane coupling agents. However, due to the extremely large dielectric constant abrupt change between the high-dielectric-constant CCTO and the low-dielectric-constant epoxy resin matrix, traditional monolayer organic interfaces cannot establish a buffer structure with a gradual transition in dielectric constant. This leads to severe accumulation of polarization charges at the interface under strong electric fields, resulting in severe local electric field distortion and electrical stress concentration, which easily induces partial discharge and early insulation breakdown, limiting the effective utilization of nonlinear conductivity characteristics. Summary of the Invention

[0005] This invention addresses the problems existing in the prior art by providing a modified calcium copper titanate nanofiber and epoxy composite dielectric material, its preparation method, and its application. The technical solution adopted in this invention is: a method for preparing modified copper titanate calcium nanofibers, characterized by comprising the following steps: Step 1: Coating the surface of copper titanate calcium nanofibers with an inorganic dielectric transition layer, wherein the inorganic dielectric transition layer is one or more of silicon dioxide layer, aluminum oxide layer and titanium oxide layer; Step 2: The copper calcium titanate nanofibers with an inorganic dielectric transition layer obtained in Step 1 are coated with an organic compatibility layer to obtain the desired modified copper calcium titanate nanofibers; the organic compatibility layer is one or more of polydopamine layer, amino resin layer and epoxy reactive polymer layer.

[0006] Furthermore, the inorganic dielectric transition layer coating on the surface of the copper titanate calcium nanofibers is prepared using one of the following methods: sol-gel method, liquid phase deposition method, and hydrolysis deposition method.

[0007] Furthermore, the preparation method of the copper calcium titanate nanofibers includes the following steps: Add the copper source, calcium source and titanium source to the glacial acetic acid solution and stir thoroughly to mix evenly; Add polyvinylpyrrolidone (PVP) and mix thoroughly to obtain an electrospinning precursor solution; Nanofibers were obtained by electrospinning, and then dried and calcined to obtain the desired copper-calcium titanate nanofibers.

[0008] Furthermore, the copper source is copper acetate monohydrate, the calcium source is calcium nitrate tetrahydrate, and the titanium source is tetrabutyl titanate. The mass ratio of copper acetate monohydrate, calcium nitrate tetrahydrate, and tetrabutyl titanate is 2.5:1:5.7; the mass ratio of tetrabutyl titanate to PVP is 6:7; and the mass ratio of glacial acetic acid to calcium nitrate tetrahydrate is 2:1.

[0009] Furthermore, the calcination process is as follows: Increase the temperature to 300–500 °C at a rate of 2 °C / min and hold for 1 hour; continue to increase the temperature to 800–1000 °C at a rate of 2 °C / min and hold for 1 hour.

[0010] A modified copper-calcium titanate nanofiber, wherein the surface of the copper-calcium titanate nanofiber is sequentially coated with an inorganic dielectric transition layer and an organic compatibility layer to form a gradient dielectric interface layer; the inorganic dielectric transition layer is one or more of silicon dioxide layer, aluminum oxide layer and titanium oxide layer; the organic compatibility layer is one or more of polydopamine layer, amino resin layer and epoxy reactive polymer layer.

[0011] An epoxy composite dielectric material includes an epoxy resin matrix and modified copper calcium titanate nanofibers dispersed in the matrix; the modified copper calcium titanate nanofibers account for 10 to 30 wt.% of the epoxy resin.

[0012] A method for preparing an epoxy composite dielectric material includes the following steps: The modified copper titanate calcium nanofibers, epoxy resin, curing agent and accelerator are thoroughly mixed evenly. The desired epoxy composite dielectric material can be obtained by vacuum degassing followed by curing; the curing process is as follows: Cured at 120 °C for 2 h, and then cured at 130 °C for 2 h.

[0013] Furthermore, the curing agent is 4-methyltetrahydrophthalic anhydride, and the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the mass ratio of epoxy resin, curing agent and accelerator is 100:80:1.6.

[0014] An application of an epoxy composite dielectric material, wherein the epoxy composite dielectric is used as an insulating component in electrical equipment and electronic devices.

[0015] The beneficial effects of this invention are: This invention obtains copper calcium titanate (CCTO) nanofibers with uniform diameter and high crystallinity through electrospinning combined with two-stage calcination; subsequently, an inorganic dielectric transition layer and an organic compatibility layer are sequentially coated in situ on the surface of the copper calcium titanate nanofibers to construct a gradient dielectric interface layer with an electric field buffer structure that satisfies the requirement that the dielectric constant decreases stepwise from the inside to the outside.

[0016] The epoxy composite dielectric material obtained by this invention significantly mitigates localized field distortions at the interface by adding modified calcium copper titanate nanofibers, which form a dynamic electric field buffer gradation between the high-dielectric inorganic filler and the low-dielectric epoxy resin matrix. This reduces abrupt changes in the electric field at the interface while maintaining the nonlinear conductivity of the calcium copper titanate nanofibers. The introduction of CCTO nanofibers, which exhibit nonlinear conductivity, results in an exponential increase in conductivity with increasing electric field strength. In high-field regions (such as material defects or areas of electric field concentration), the fibers rapidly form localized conductive channels, actively diverting excess charge and dynamically balancing the electric field distribution. Consequently, the resulting epoxy composite dielectric material possesses excellent comprehensive electromechanical properties and adaptive electric field regulation characteristics.

[0017] The calcium titanate fiber network with a gradient dielectric interface in the epoxy composite dielectric material obtained by this invention effectively dissipates the interface space charge through the carrier migration mechanism. Combined with nonlinear conductivity characteristics, it shortens the charge dissipation time, inhibits dielectric aging, and extends the service life of the equipment. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the preparation method of the epoxy composite dielectric material of the present invention.

[0019] Figure 2 The figures show the conductivity variation curves of Embodiments 1, 2, and 3 and Comparative Examples 1 and 2 of the present invention under different electric field intensities.

[0020] Figure 3 The dielectric constants are those of Embodiments 1, 2, and 3 and Comparative Examples 1 and 2 of the present invention.

[0021] Figure 4 The breakdown probability curves for Embodiments 1, 2, and 3 and Comparative Examples 1 and 2 of the present invention under different electric field intensities are shown.

[0022] Figure 5 These are the stress-strain curves of Embodiments 1, 2, and 3 and Comparative Examples 1 and 2 of the present invention. Detailed Implementation

[0023] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0024] like Figure 1 As shown, a method for preparing modified calcium copper titanate nanofibers includes the following steps: Step 1: Coating the surface of calcium copper titanate nanofibers with an inorganic dielectric transition layer, wherein the inorganic dielectric transition layer is one or more of silicon dioxide, alumina, and titanium oxide layers; wherein the preparation method of calcium copper titanate nanofibers includes the following steps: Add the copper, calcium, and titanium sources to the glacial acetic acid solution and mix thoroughly. Add one substance at a time, ensuring the previous substance is fully dissolved and no powdery precipitate appears before adding the next. Magnetic stirring is used throughout the process. The copper source is copper acetate monohydrate, the calcium source is calcium nitrate tetrahydrate, and the titanium source is tetrabutyl titanate. The mass ratio of copper acetate monohydrate, calcium nitrate tetrahydrate, and tetrabutyl titanate is 2.5:1:5.7; the mass ratio of tetrabutyl titanate to PVP is 6:7; and the mass ratio of glacial acetic acid to calcium nitrate tetrahydrate is 2:1.

[0025] Add polyvinylpyrrolidone (PVP) and mix thoroughly to obtain the electrospinning precursor solution. During the mixing process, add the PVP slowly in three batches at 5-minute intervals to prevent the PVP from agglomerating in the solution system, while maintaining magnetic stirring throughout. Place the electrospinning precursor solution in a vacuum drying oven to remove air bubbles introduced during the addition of chemicals and stirring.

[0026] Nanofibers were obtained by electrospinning, and then dried and calcined to obtain the desired calcium copper titanate nanofibers. A layer of aluminum foil was uniformly wrapped around the surface of the receiving roller of the electrospinning machine to ensure a smooth surface. The position of the feed device was then adjusted to ensure a uniform electric field distribution between the tip of the stainless steel needle and the receiving roller. The precursor solution was injected into the syringe, and after attaching the stainless steel needle, it was fixed to the feed device. The needle was connected to the positive terminal of the high-voltage power supply, and the receiving roller was connected to the negative terminal. After setting the electrospinning ambient temperature, humidity, and feed speed, the feed device, high-voltage power supply, and receiving device were started. Observation of a stable Taylor cone forming at the tip of the needle indicated that the electrospinning process was normal. After electrospinning, the nanofibers were placed in a drying oven to thoroughly remove residual solvent and moisture.

[0027] The calcination process is as follows: Increase the temperature to 300–500 °C at a rate of 2 °C / min and hold for 1 hour; continue to increase the temperature to 800–1000 °C at a rate of 2 °C / min and hold for 1 hour.

[0028] The inorganic dielectric transition layer coated on the surface of calcium copper titanate nanofibers is prepared using one of the following methods: sol-gel method, liquid phase deposition method, and hydrolysis deposition method. For example, the liquid phase deposition method is as follows: Copper calcium titanate nanofibers were added to a dispersion containing an inorganic dielectric precursor, and the precursor was uniformly adsorbed onto the nanofiber surface under stirring. Subsequently, a hydrolysis-condensation reaction was carried out to form a continuous inorganic dielectric transition layer in situ on the surface of the copper calcium titanate nanofibers. The inorganic dielectric precursor was one or more of tetraethyl orthosilicate, aluminum isopropoxide, and tetrabutyl titanate.

[0029] Step 2: The copper-calcium titanate nanofibers with an inorganic dielectric transition layer obtained in Step 1 are coated with an organic compatibility layer to obtain the desired modified copper-calcium titanate nanofibers. The organic monomer is one or more of dopamine, amino resin monomers, or epoxy reactive monomers. The organic compatibility layer is one or more of polydopamine layers, amino resin layers, and epoxy reactive polymer layers. The copper-calcium titanate nanofibers with the inorganic dielectric transition layer are added to the organic monomer solution and undergo in-situ self-polymerization under alkaline conditions to form a continuous organic compatibility layer on the surface of the inorganic dielectric transition layer.

[0030] The obtained modified copper titanate calcium nanofibers were washed sequentially with ethanol and deionized water, and dried under vacuum. After standing, they were filtered in batches using a Buchner funnel, washed with deionized water to remove residual solvent and unreacted precursors. After filtration, they were placed in a drying oven and dried at a higher temperature.

[0031] Modified copper-calcium titanate nanofibers, wherein the surface of the copper-calcium titanate nanofibers is sequentially coated with an inorganic dielectric transition layer and an organic compatibility layer to form a gradient dielectric interface layer; the inorganic dielectric transition layer is one or more of silicon dioxide, alumina, and titanium oxide; the organic compatibility layer is one or more of polydopamine, amino resin, and epoxy reactive polymer.

[0032] An epoxy composite dielectric material includes an epoxy resin matrix and modified copper calcium titanate nanofibers dispersed in the matrix; the modified copper calcium titanate nanofibers account for 10 to 30 wt.% of the epoxy resin.

[0033] A method for preparing an epoxy composite dielectric material includes the following steps: The modified copper titanate calcium nanofibers, epoxy resin, curing agent and accelerator are thoroughly mixed; the curing agent is 4-methyltetrahydrophthalic anhydride and the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the mass ratio of epoxy resin, curing agent and accelerator is 100:80:1.6.

[0034] The desired epoxy composite dielectric material can be obtained by vacuum degassing followed by curing; the curing process is as follows: Cured at 120 °C for 2 h, and then cured at 130 °C for 2 h.

[0035] Example 1 A method for preparing modified copper calcium titanate nanofibers includes the following steps: First, calcium copper titanate nanofibers are prepared: Mix 80 mL of anhydrous ethanol and 1.6 mL of glacial acetic acid, and turn on magnetic stirring at 250 rpm; Weigh 2.12 g of copper acetate monohydrate, 0.84 g of calcium nitrate tetrahydrate and 2.4 g of tetrabutyl titanate and add them to the above system. Each time a new drug is added, the previous drug should be observed to be fully dissolved without the appearance of powdery precipitate. During this period, maintain magnetic stirring at a speed of 250 rpm.

[0036] Weigh 2.8 g of PVP and add it to the system in three slow additions at 5-minute intervals to prevent PVP from agglomerating in the solution. Maintain magnetic stirring at 250 rpm throughout the process. Seal the resulting system further and then continuously stir at 250 rpm at room temperature to obtain a bright green classic electrospinning precursor solution. Place the obtained electrospinning precursor solution in a 30°C vacuum drying oven and evacuate it. Let it stand for 30 minutes to remove any bubbles introduced during the addition of chemicals and stirring.

[0037] A layer of aluminum foil was evenly wrapped around the surface of the receiving roller of the electrospinning machine to ensure a smooth surface. The position of the feed device was then adjusted so that the distance between the tip of the stainless steel needle and the receiving roller was 18 cm to ensure a uniform electric field distribution between them. A 20 mL syringe containing the precursor solution was injected and fitted with a No. 21 stainless steel needle, which was then fixed to the feed device. The needle was connected to the positive terminal (+15 kV) of the high-voltage power supply, and the receiving roller was connected to the negative terminal (-9 kV). The electrospinning environment was set to a temperature of 20 ℃, a relative humidity below 20%, a feed speed of 0.15 mm / min, and the roller rotation speed on the receiving device was set to 300 rpm. The feed device, high-voltage power supply, and receiving device were then started. Observation of a stable Taylor cone forming at the needle tip indicates that the electrospinning process is normal.

[0038] The obtained nanofiber film was dried in a vacuum drying oven at 60 °C under normal pressure for 2 hours to completely remove residual solvent and moisture. The dried fiber film was then subjected to two-stage calcination in a muffle furnace. The first stage involved heating to 400 °C at a rate of 2 °C / min and holding at that temperature for 1 hour. The second stage involved further heating to 900 °C at a rate of 2 °C / min and holding at that temperature for 1 hour. After calcination, the heating was turned off, and the muffle furnace was allowed to cool naturally to room temperature.

[0039] Step 1: Add copper calcium titanate nanofibers to an anhydrous ethanol solution of tetraethyl orthosilicate. Under continuous stirring, the first dielectric precursor is adsorbed onto the surface of the nanofibers. By controlling the hydrolysis-condensation reaction, a continuous silica layer is formed in situ on the surface of the copper calcium titanate nanofibers as an inorganic dielectric transition layer.

[0040] Step 2: Add copper-calcium titanate nanofibers coated with an inorganic dielectric transition layer to a dopamine monomer solution. In a weakly alkaline aqueous solution, control the in-situ self-polymerization of dopamine monomers on the surface of the inorganic dielectric transition layer to form a continuously coated polydopamine layer as an organic compatibility layer, thereby constructing copper-calcium titanate nanofibers with a gradient dielectric interface layer. The copper-calcium titanate nanofibers with the gradient dielectric interface layer are sequentially washed with ethanol and deionized water, and dried under vacuum to obtain functional nanofibers with a stable gradient dielectric interface. The suspension is allowed to stand, filtered in batches using a Buchner funnel, washed with deionized water to remove residual solvent and unreacted coupling agent, and then placed in a drying oven for further drying to remove moisture, thus obtaining modified copper-calcium titanate nanofibers.

[0041] A method for preparing an epoxy composite dielectric material includes the following steps: 1 g of modified copper titanate calcium nanofibers, 10 g of epoxy resin, 8 g of 4-methyltetrahydrophthalic anhydride, and 0.16 g of 2,4,6-tris(dimethylaminomethyl)phenol were mixed and stirred until fully combined.

[0042] The mixed modified copper titanate calcium nanofiber / epoxy resin system was placed in a vacuum drying oven and degassed at 60 °C for 1 hour to remove internal air bubbles.

[0043] The modified calcium copper titanate nanofiber / epoxy resin system was poured into a stainless steel mold and then transferred to an oven for stepped temperature curing. The first stage was curing at 120 °C for 2 hours, and the second stage was curing at 130 °C for 2 hours. After the oven cooled naturally, a CCTO nanofiber / epoxy resin composite dielectric with a filler content of 10% was obtained.

[0044] Example 2 The preparation method of modified copper calcium titanate nanofibers in this embodiment is the same as that in Example 1. The difference is that the amount of modified copper calcium titanate nanofibers added during the preparation of epoxy composite dielectric material is 2 g, resulting in a CCTO nanofiber / epoxy resin composite dielectric with a filler content of 20%.

[0045] Example 3 The preparation method of modified copper calcium titanate nanofibers in this embodiment is the same as that in Example 1. The difference is that the amount of modified copper calcium titanate nanofibers added during the preparation of epoxy composite dielectric material is 3 g, resulting in a CCTO nanofiber / epoxy resin composite dielectric with a filler content of 30%.

[0046] Comparative Example 1 A method for preparing an epoxy dielectric material includes the following steps: Mix 10 g of epoxy resin, 8 g of 4-methyltetrahydrophthalic anhydride, and 0.16 g of 2,4,6-tris(dimethylaminomethyl)phenol and stir until fully mixed.

[0047] The mixed epoxy resin system was placed in a vacuum drying oven and degassed at 60 °C for 1 hour to remove internal air bubbles.

[0048] The epoxy resin system was poured into a stainless steel mold and then transferred to an oven for stepped temperature curing. The first stage involved curing at 120°C for 2 hours, and the second stage involved curing at 130°C for 2 hours. After the oven cooled naturally, the epoxy resin dielectric was obtained.

[0049] Comparative Example 2 A method for preparing an epoxy composite dielectric material includes the following steps: 1 g of calcium copper titanate nanofibers, 10 g of epoxy resin, 8 g of 4-methyltetrahydrophthalic anhydride, and 0.16 g of 2,4,6-tris(dimethylaminomethyl)phenol were mixed and stirred until fully combined.

[0050] The mixed copper titanate calcium nanofiber / epoxy resin system was placed in a vacuum drying oven and degassed at 60 °C for 1 hour to remove internal air bubbles.

[0051] The copper-calcium titanate nanofiber / epoxy resin system was poured into a stainless steel mold and then transferred to an oven for stepped temperature curing. The first stage was curing at 120 °C for 2 hours, and the second stage was curing at 130 °C for 2 hours. After the oven cooled naturally, a copper-calcium titanate nanofiber / epoxy resin composite dielectric with a filler content of 10% was obtained.

[0052] The preparation method of calcium copper titanate nanofibers is as described in Example 1.

[0053] DC conductivity tests were performed on the epoxy resin composite dielectric materials obtained in Examples 1, 2, and 3, and Comparative Examples 1 and 2. Logarithms of the electric field strength and current density were taken, and linear fitting was performed. The results are as follows: Figure 2 As shown in the figure, in the composite dielectric materials obtained in Examples 1, 2, and 3, the spacing between the nanofibers decreases with the increase of the modified calcium copper titanate nanofiber content. Under high field strength, charge carriers can overcome the potential barrier to form tunneling current, exhibiting excellent nonlinear conductivity characteristics. With the increase of filler content, the nonlinear threshold field strength of the composite material gradually decreases, while the nonlinear coefficient gradually increases.

[0054] In contrast, the pure epoxy resin system in Comparative Example 1 does not possess nonlinear conductivity characteristics; in Comparative Example 2, due to the lack of gradient dielectric layer modification on the surface of calcium copper titanate nanofibers, the filler is prone to agglomeration and has many interface defects, making it difficult to effectively construct complete nonlinear transport channels under low filling conditions, and thus it does not exhibit obvious nonlinear conductivity characteristics.

[0055] The dielectric properties of the epoxy resin composite dielectric materials obtained in Examples 1, 2, and 3 and Comparative Examples 1 and 2 were tested, and their dielectric constants are as follows: Figure 3As shown in the figure, the dielectric constant of each sample decreases slowly with increasing applied electric field frequency. At the same frequency, with increasing modified copper titanate calcium nanofiber content, the dielectric constant of the composite material increases significantly due to the one-dimensional gradient interface microcapacitor effect and the gradual and reasonable transition of polarization at the two-phase interface. However, in Comparative Example 2, the copper titanate calcium nanofiber surface lacks an inorganic / organic bilayer gradient dielectric transition layer design, resulting in a large dielectric abrupt change between the inorganic and organic phases. This leads to severe accumulation of polarization charge at the abrupt interface, causing significant losses. Furthermore, the poor compatibility between the two phases results in a lack of significant improvement in dielectric constant, while losses increase sharply.

[0056] DC breakdown tests were performed on the epoxy resin composite dielectric materials obtained in Examples 1, 2, and 3, and Comparative Examples 1 and 2. The breakdown voltage of the samples was fitted using a hyperbolic Weibull distribution, and the results are as follows: Figure 4 As shown in the figure, the dielectric constant of the calcium copper titanate nanofibers is much greater than that of the epoxy resin matrix. Dielectric mismatch can cause electric field distortion at the interface and may induce pre-breakdown electrical trees. In the example, the modified calcium copper titanate nanofibers, with their inorganic / organic bilayer buffer layer, exhibit a gradual decrease in dielectric constant from the inside out, effectively distributing and mitigating the electric field at the interface. In contrast, the calcium copper titanate nanofibers in the comparative example lack this inorganic / organic bilayer buffer layer, resulting in poor compatibility, numerous local defects, and a significant decrease in the breakdown field strength due to their lack of modification.

[0057] Mechanical properties of the epoxy resin composite dielectric materials obtained in Examples 1, 2, and 3 and Comparative Examples 1 and 2 were tested, and the stress-strain curves are shown below. Figure 5 As shown in the figure, the high compatibility between the organic compatibility layer on the surface of the modified copper titanate calcium nanofibers and the epoxy resin matrix significantly enhances the interfacial adhesion, thereby improving the interaction between epoxy polymer molecular chains. At low filler content (Example 1), its tensile strength is significantly higher than that of Comparative Example 1 and Comparative Example 2. At high filler content (Examples 2 and 3), the mechanical properties decrease somewhat, but are still significantly better than the composite dielectric obtained in Comparative Example 2.

[0058] The epoxy resin composite dielectric material obtained in this invention constructs an inorganic dielectric transition layer and an organic compatibility layer with progressively decreasing dielectric constants from the inside out between calcium copper titanate nanofibers and the epoxy resin matrix, forming an interfacial gradient polarization transition matching. This gradient interfacial layer acts as an electric field buffer structure, effectively distributing and mitigating the locally concentrated electric field at the interface of high dielectric abrupt change (the interface between the metal fiber and the epoxy resin), significantly reducing the accumulation of interfacial polarization charge and the interfacial Maxwell-Wagner effect. This not only significantly suppresses partial discharge and electric tree initiation under high field strength but also effectively protects and maintains the nonlinear conductivity modulation characteristics of the one-dimensional calcium copper titanate nanofibers. By introducing calcium copper titanate nanofibers with nonlinear conductivity characteristics, the conductivity increases exponentially with the electric field strength. In high field strength regions (such as material defects or areas of electric field concentration), the fibers rapidly form local conductive channels, actively diverting excess charge and dynamically balancing the electric field distribution. Compared with traditional linear conductive fillers, it can significantly suppress electric field distortion and reduce the probability of partial discharge without relying on high filling volume.

[0059] Traditional epoxy resins are prone to accumulating space charge due to interfacial polarization, which accelerates dielectric aging. Modified copper-calcium titanate nanofiber networks coated with gradient dielectric interfaces effectively dissipate interfacial space charge through carrier migration mechanisms. Combined with nonlinear conductivity characteristics, this shortens charge dissipation time, inhibits dielectric aging, and extends equipment lifespan.

Claims

1. A method for preparing modified calcium copper titanate nanofibers, characterized in that, Includes the following steps: Step 1: Coating the surface of copper titanate calcium nanofibers with an inorganic dielectric transition layer, wherein the inorganic dielectric transition layer is one or more of silicon dioxide layer, aluminum oxide layer and titanium oxide layer; Step 2: The copper calcium titanate nanofibers with an inorganic dielectric transition layer obtained in Step 1 are coated with an organic compatibility layer to obtain the desired modified copper calcium titanate nanofibers; the organic compatibility layer is one or more of polydopamine layer, amino resin layer and epoxy reactive polymer layer.

2. The method for preparing modified copper titanate calcium nanofibers according to claim 1, characterized in that, The inorganic dielectric transition layer coating on the surface of the copper titanate calcium nanofibers is prepared by one of the following methods: sol-gel method, liquid phase deposition method, and hydrolysis deposition method.

3. The method for preparing modified copper titanate calcium nanofibers according to claim 1, characterized in that, The preparation method of the copper titanate calcium nanofibers includes the following steps: Add the copper source, calcium source and titanium source to the glacial acetic acid solution and stir thoroughly to mix evenly; Add polyvinylpyrrolidone (PVP) and mix thoroughly to obtain an electrospinning precursor solution; Nanofibers were obtained by electrospinning, and then dried and calcined to obtain the desired copper-calcium titanate nanofibers.

4. The method for preparing modified copper titanate calcium nanofibers according to claim 3, characterized in that, The copper source is copper acetate monohydrate, the calcium source is calcium nitrate tetrahydrate, and the titanium source is tetrabutyl titanate. The mass ratio of copper acetate monohydrate, calcium nitrate tetrahydrate, and tetrabutyl titanate is 2.5:1:5.7; the mass ratio of tetrabutyl titanate to PVP is 6:7; and the mass ratio of glacial acetic acid to calcium nitrate tetrahydrate is 2:

1.

5. The method for preparing modified copper titanate calcium nanofibers according to claim 3, characterized in that, The calcination process is as follows: Increase the temperature to 300–500 °C at a rate of 2 °C / min and hold for 1 hour; continue to increase the temperature to 800–1000 °C at a rate of 2 °C / min and hold for 1 hour.

6. Modified calcium copper titanate nanofibers obtained by any one of the preparation methods described in claims 1 to 5, characterized in that, The surface of the copper titanate calcium nanofibers is sequentially coated with an inorganic dielectric transition layer and an organic compatibility layer to form a gradient dielectric interface layer; the inorganic dielectric transition layer is one or more of silicon dioxide, aluminum oxide and titanium oxide; the organic compatibility layer is one or more of polydopamine, amino resin and epoxy reactive polymer.

7. An epoxy composite dielectric material, characterized in that, It includes an epoxy resin matrix and modified copper calcium titanate nanofibers as described in claim 6 dispersed in the matrix; the modified copper calcium titanate nanofibers account for 10 to 30 wt.% of the epoxy resin mass.

8. The method for preparing an epoxy composite dielectric material as described in claim 6, characterized in that, Includes the following steps: The modified copper titanate calcium nanofibers, epoxy resin, curing agent and accelerator are thoroughly mixed evenly. The desired epoxy composite dielectric material can be obtained by vacuum degassing followed by curing; the curing process is as follows: Cured at 120 °C for 2 h, and then cured at 130 °C for 2 h.

9. The method for preparing an epoxy composite dielectric material according to claim 8, characterized in that, The curing agent is 4-methyltetrahydrophthalic anhydride, and the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol; the mass ratio of epoxy resin, curing agent and accelerator is 100:80:1.

6.

10. The application of the epoxy composite dielectric material as described in claim 7, characterized in that, The epoxy composite dielectric is used as an insulating component in electrical equipment and electronic devices.